Design and implementation of control system for remotely surface vehicle in aquaculture environmental monitoring - Sutrisno, Imam; Rahmat, Mohammad Basuki (Edelweiss Applied Science and Technology, 2025)
This study aims to develop and evaluate the RSV EMAS (Environmental Monitoring Aquaculture System), an autonomous surface vehicle designed for real-time water quality monitoring in aquaculture ponds. The primary purpose is to support smallholder shrimp farmers in Indonesia with affordable and reliable technology to improve farm management and sustainability. The design methodology includes mechanical and electronic integration of a GPS-guided mobile platform, PID-controlled navigation, and calibrated water quality sensors (DO, pH, temperature, turbidity, salinity, depth). Data are wirelessly transmitted using LoRa to a custom mobile application for visualization. Field testing was conducted in shrimp ponds across East Java. Findings indicate that the RSV EMAS achieves sensor measurement accuracy within ±5% of industry-standard equipment, with consistent path tracking and minimal drift. The system reduces manual labor by 85% and increases sampling frequency by a factor of four. The study concludes that RSV EMAS presents a cost-effective, field-ready solution for precision aquaculture. Practical implications include improved decision-making for pond management, enhanced shrimp health, and the potential for scaling smart farming technologies in resource-constrained settings.